2016
DOI: 10.1016/j.jweia.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Inviscid approach for upwind sails aerodynamics. How far can we go?

Abstract: a b s t r a c tThis work presents a full-scale experimental study of a yacht rig and sails in real upwind sailing conditions and a comparison with Fluid Structure Interaction (FSI) simulations with the ARAVANTI model (Finite Element Method for the structure and Vortex Lattice Method for the fluid). A specific on-board instrumentation system simultaneously measures loads in the rig and sails, sailing data (wind, boat attitude and speed) and the shape of sails in real navigation conditions (flying shape). Flying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Some studies [2,7,9] found bend-twist coupling of the foils to be important. Experience with large flow induced deformation of thin structures can also be found on the aerodynamic of sailing boats, where recent work [15][16][17][18][19] investigated FSI simulation of yacht sails.…”
Section: State Of the Artmentioning
confidence: 99%
“…Some studies [2,7,9] found bend-twist coupling of the foils to be important. Experience with large flow induced deformation of thin structures can also be found on the aerodynamic of sailing boats, where recent work [15][16][17][18][19] investigated FSI simulation of yacht sails.…”
Section: State Of the Artmentioning
confidence: 99%
“…Otherwise, the numerical optimization procedure can produce an unphysical solution, even if the model is actually fairly accurate in the neighborhood of the physical optimum. In the present case, the problem could be remedied by means of an ad hoc penalization of the performance function; for instance one could add a righting moment penalty term or artificially decrease the performance for trimmings likely to produce a detached flow (Aubin et al, 2016).…”
Section: Inviscid Flow Solvermentioning
confidence: 99%